Strafzumessung und Doppelverwertung - Seelmann, Martin (sui generis Verlag, 2024)
Long before the Swiss Criminal Code was enacted with its provisions on sentencing, the assessment of the specific punishment in individual cases was seen as the most difficult and demanding, but also the most important task of the court. The aim of this treatise is to examine the sentencing in In general and the ban on double use in particular, “to draw up a guide to a more verifiable sentencing system”. In the first part, Switzerland's sentencing law is examined in its historical, dogmatic and practical dimensions and condensed into a test program. In the second part, the ban on double use is discussed, analyzed and incorporated into the concept of sentencing developed in the first part.